Autophagy as an emerging target for COVID-19: lessons from an old friend, chloroquine. Issue 12 (1st December 2020) - Bonam, Srinivasa Reddy; Muller, Sylviane; Bayry, Jagadeesh; Klionsky, Daniel J.
ABSTRACT: During the last week of December 2019, Wuhan (China) was confronted with the first case of respiratory tract disease 2019 (coronavirus disease 2019, COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Due to the rapid outbreak of the transmission (~3.64 million positive cases and high mortality as of 5 May 2020), the world is looking for immediate and better therapeutic options. Still, much information is not known, including origin of the disease, complete genomic characterization, mechanism of transmission dynamics, extent of spread, possible genetic predisposition, clinical and biological diagnosis, complete details of disease-induced pathogenicity, and possible therapeutic options. Although several known drugs are already under clinical evaluation with many in repositioning strategies, much attention has been paid to the aminoquinoline derivates, chloroquine (CQ) and hydroxychloroquine (HCQ). These molecules are known regulators of endosomes/lysosomes, which are subcellular organelles central to autophagy processes. By elevating the pH of acidic endosomes/lysosomes, CQ/HCQ inhibit the autophagic process. In this short perspective, we discuss the roles of CQ/HCQ in the treatment of COVID-19 patients and propose new ways of possible treatment for SARS-CoV-2 infection based on the molecules that selectivity target autophagy.Abbreviation: ACE2: angiotensin I converting enzyme 2; CoV: coronavirus; CQ: chloroquine; ER: endoplasmic reticulum; HCQ: hydroxychloroquine; MERS-CoV: Middle East respiratory syndrome coronavirus; SARS-CoV: severe acute respiratory syndrome coronavirus; SARS-CoV-2: severe acute respiratory syndrome coronavirus 2